IL-33 and Superantigenic Activation of Human Lung Mast Cells Induce the Release of Angiogenic and Lymphangiogenic Factors - Leonardo Cristinziano; Remo Poto; Gjada Criscuolo; Anne Lise Ferrara; Maria Rosaria Galdiero; Luca Modestino; Stefania Loffredo; Amato de Paulis; Gianni Marone; Giuseppe Spadaro; Gilda Varricchi (Cells, 2021)
Human lung mast cells (HLMCs) express the high-affinity receptor FcεRI for IgE and are strategically located in different compartments of human lung, where they play a role in several inflammatory disorders and cancer. Immunoglobulin superantigens (e.g., protein A of Staphylococcus aureus and protein L of Peptostreptococcus magnus) bind to the variable regions of either the heavy (VH3) or light chain (κ) of IgE. IL-33 is a cytokine expressed by epithelial cells that exerts pleiotropic functions in the lung. The present study investigated whether immunoglobulin superantigens protein A and protein L and IL-33 caused the release of inflammatory (histamine), angiogenic (VEGF-A) and lymphangiogenic (VEGF-C) factors from HLMCs. The results show that protein A and protein L induced the rapid (30 min) release of preformed histamine from HLMCs. By contrast, IL-33 did not induce the release of histamine from lung mast cells. Prolonged incubation (12 h) of HLMCs with superantigens and IL-33 induced the release of VEGF-A and VEGF-C. Preincubation with IL-33 potentiated the superantigenic release of histamine, angiogenic and lymphangiogenic factors from HLMCs. Our results suggest that IL-33 might enhance the inflammatory, angiogenic and lymphangiogenic activities of lung mast cells in pulmonary disorders.